2021
DOI: 10.3389/fmicb.2021.670016
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T-Cell Mediated Control of HIV-1 in a Unique Cohort With Low Viral Loads

Abstract: A unique population of HIV-1 infected individuals can control infection without antiretroviral therapy. These individuals fall into a myriad of categories based on the degree of control (low or undetectable viral load), the durability of control over time and the underlying mechanism (i.e., possession of protective HLA alleles or the absence of critical cell surface receptors). In this study, we examine a cohort of HIV-1 infected individuals with a documented history of sustained low viral loads in the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…During chronic infection, increased upregulation of ICRs results in T-cell exhaustion, a spectrum of progressively impaired effector functions which cause a hierarchical loss of T cell functionality. Our group previously demonstrated that in vivo viral control corresponds to ex vivo suppression of viral replication in a cohort of HIV-1 controllers (51). In the current study, a cohort of HIV-1 controllers who lost the ability to control viral replication, and were subsequently placed on ART after enrollment, presents a unique opportunity to observe real time changes associated with HIV-1 viral replication and T cell exhaustion within the same subject.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During chronic infection, increased upregulation of ICRs results in T-cell exhaustion, a spectrum of progressively impaired effector functions which cause a hierarchical loss of T cell functionality. Our group previously demonstrated that in vivo viral control corresponds to ex vivo suppression of viral replication in a cohort of HIV-1 controllers (51). In the current study, a cohort of HIV-1 controllers who lost the ability to control viral replication, and were subsequently placed on ART after enrollment, presents a unique opportunity to observe real time changes associated with HIV-1 viral replication and T cell exhaustion within the same subject.…”
Section: Discussionmentioning
confidence: 99%
“…This ex vivo control was shown to be mediated by CD8+ T-cells. Further, CD8+ T-cells in these controllers maintained levels of activation markers and the exhaustion marker PD-1 equivalent to uninfected individuals, unlike PLWH without a history of control who exhibited the expected increase in activation and PD-1 (51).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation